Impact of Legal Exclusion on Water Service Delivery in an Urban Slum Community in Mumbai, India: Mechanisms and Inequalities - Lubeck-Schricker, Maya I. (Tufts Archival Research Center, 2020)
The primary aim of this study is to understand how legal status (notification) impacts water service delivery within one geographically contiguous slum community in Mumbai that includes a mix of notified (i.e., “legal”) and non-notified (i.e., illegal) households. We found that non-notified status adversely affects water quantity used by individuals in a household.The second aim of this study is to understand how different approaches to interpreting and operationalizing notification impact the association between legal status and water quantity. More specifically, we compare two approaches to interpreting legal status. In the community’s perception of legal status,notification (or lack thereof) is perceived to apply to geographically contiguous clusters of households. In contrast, using the government’s technical definition,notification is supposed to be assessed and decided for each individual household based on documentation of residence in the community prior to a pre-decided cutoff date. We found that the association of legal status with water quantity is strongest when notification is defined using the community’s perception of which areas in the settlement are notified and non-notified, because delivery of water requires development of substantial infrastructure in a manner that is often geographically constrained.